The Role of Government Health and Education Expenditure on Economic Growth in OPEC oil Exporting Countries - Ebrahim Anvari (Journal of Global Pharma Technology, 2018)
Economic growth is one of the goals of development in economic plans of every country. Achieving self- development in OPEC member Oil - exporting countries takes precise awareness of the amount of economic variables. Among these variables, oil revenues, total government expenditure, government expenditure for education and  government expenditure for health could be mentioned.In this research using panel data studies of relationship between health expenditure and education expenditure and economic growth in OPEC oil-exporting countries for 2004 to 2014. Hence, panel data method has been applied in order to estimate  models and panel var method has been applied in order to examine the causality relationships between variables. The results shows a positive meaningful relationship between oil revenues, total government expenditure, government expenditure for education, government expenditure in health, and economic growth of OPEC oil-exporting countries in the studied period. Furthermere, the result of Granger Causality test suggest that there was one –side relationship of economic growth with government expenditure for health in OPEC member countries in the studied period.Keywords: Economic growth, Government expenditure, Oil revenue JEL: H51, H40, C13.